Expression of Peroxisome Proliferator-Activated Receptor alpha (PPARα) in somatotropinomas: Relationship with Aryl hydrocarbon receptor Interacting Protein (AIP) and in vitro effects of fenofibrate in GH3 cells. (5th May 2016) - Rotondi, Sandra; Modarelli, Alessio; Oliva, Maria-Antonietta; Rostomyan, Liliya; Sanita, Patrizia; Ventura, Luca; Daly, Adrian F.; Esposito, Vincenzo; Angelucci, Adriano; Arcella, Antonietta; Giangaspero, Felice; Beckers, Albert; et al.
Abstract: Purpose: To search for a possible role of Peroxisome Proliferator-Activated Receptor α (PPARα), a molecular partner of the Aryl hydrocarbon receptor Interacting Protein (AIP), in somatotropinomas. Methods: Tumours from 51 acromegalic patients were characterized for PPARα and AIP expression by immunohistochemistry (IHC) and/or Real Time RT-PCR. Data were analysed according to tumour characteristics and pre-operative treatment with somatostatin analogues (SSA). The effects of fenofibrate were studied in GH3 cells in vitro . Results: PPARα was expressed in most somatotropinomas. A modest relationship was found between PPARα and AIP expression, both being significantly higher in the presence of pre-operative SSA. However, only AIP expression was influenced by the response to treatment. Dual effects of fenofibrate were observed in GH3 cells, consisting of cell growth inhibition and an increase in GH secretion inhibited by octreotide. Conclusions: PPARα is a new player in somatotropinomas. Potential interactions between PPARα agonists and SSA may deserve further investigation. Highlights: PPARα, a molecular partner of AIP, is commonly expressed in somatotropinomas. PPARα is unlikely to play a major role in AIP-related somatotroph tumorigenesis. Somatostatin analogues (SSA) increase PPARα expression in somatotroph tumours. Fenofibrate has differential effects on GH3 cell growth and hormone secretion. Potential interactions between PPRAα agonists and SSA deserve further investigation.